2017
DOI: 10.1073/pnas.1703355114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating optimal therapy robustness by virtual expansion of a sample population, with a case study in cancer immunotherapy

Abstract: Cancer is a highly heterogeneous disease, exhibiting spatial and temporal variations that pose challenges for designing robust therapies. Here, we propose the VEPART (Virtual Expansion of Populations for Analyzing Robustness of Therapies) technique as a platform that integrates experimental data, mathematical modeling, and statistical analyses for identifying robust optimal treatment protocols. VEPART begins with time course experimental data for a sample population, and a mathematical model fit to aggregate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 70 publications
(116 reference statements)
0
68
0
Order By: Relevance
“…al. [2]. Three key model parameters were chosen: tumor cell net proliferation (r), tumor cell transfection rate (ÎČ), and tumor cell killing rate by the T cells (k), and the generated distributions for each of these parameters are shown in Figure 2.…”
Section: Generating Virtual Mice Cohortsmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [2]. Three key model parameters were chosen: tumor cell net proliferation (r), tumor cell transfection rate (ÎČ), and tumor cell killing rate by the T cells (k), and the generated distributions for each of these parameters are shown in Figure 2.…”
Section: Generating Virtual Mice Cohortsmentioning
confidence: 99%
“…The model flowchart and equations are shown in Figure 4, and model parameters are listed in Table 1. [1], transfected cells dI/dt [2], the vaccine dV/dt [3], and T-cells dT/dt [4].…”
Section: Quick Guide To the Equationsmentioning
confidence: 99%
“…For combined immunotherapy and chemotherapy, de Pillis et al [32] developed an ODE system that predicted which treatment protocols would result in tumour elimination. There are also a handful of examples where deterministic models have also been used to improve chemotherapy delivery from sustained-release systems [33,34], Mathematical modelling has also been used to determine optimal dosage protocols for oncolytic virotherapy and immunotherapy [35][36][37][38]. Using ODEs calibrated with experimental data, Barish et al [38] demonstrated that lower oncolytic virus doses combined with higher dendritic cell doses resulted in an optimal robust therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the effects of spatial heterogeneity in drug concentration 42 , vascular structure and heterogeneous host environment 7,43 , cell packing density 44 , intrinsic heterogeneity in cell phenotypes and cell cycles [45][46][47][48][49][50] on the effectiveness of treatment and acquired drug resistance 51,52 have been systematically studied. Computational tools for treatment optimization have been devised [53][54][55][56] and data-based platform has been developed to assess robustness of treatment 57 .…”
Section: Introductionmentioning
confidence: 99%